ESTET – NEW INNOVATIVE SPECIALTY FOR MASTER STUDENTS - Hnatov, A.; Arhun, Shch.; Ulyanets, O.; Гнатов, А. В.; Аргун, Щ. В.; Ульянець, О. А. (Харьковский национальный автомобильно-дорожный университет, 2018)
Currently, new educational reforms are intensively being implemented in Ukraine. This is achieved, including, by the development and implementation of new innovative joint training programs. Goal. To improve higher education in accordance with the changing needs of economic and social spheres in the road transport sector due to the growth of innovative energy-efficient and energy-saving technologies. To increase the competitiveness of graduates in em-ployment and the productive cooperation between the universities. To reduce energy consumption and to replace traditional sources by «green» forms of energy in the transport sector as well. Methodology. The analysis of existing joint educational programs for masters was con-ducted. There was accomplished the analysis and monitoring of the labor market with the determination of its urgent and future needs, taking into account the development of modern electric transport. Results. The project for implementation of the new innovative master’s program in the specialty «Energy-saving technologies in transport» (ESTeT) has been developed. We have proposed the structure of a new specialty. The work packages that address specific tasks in the overall system of the ESTeT project implementation have been briefly described. The division of the new master's specialty into its constituting structural elements has been carried out. Originality. We proposed the new innovative educational joint program for masters ESTeT. Practical value. The implementation of new innovative joint specialties in the field of higher education in Ukraine provides an opportunity to increase the level of Ukrainian higher education itself. This will allow students to acquire the appropriate competencies in the field of study and expand their applications. Also, obtaining two diplomas (Ukrainian and European) by students will sig-nificantly expand their employment opportunities.
ESTET – НОВА ІННОВАЦІЙНА СПЕЦІАЛЬНІСТЬ ДЛЯ МАГІСТРІВ
ESTET – НОВАЯ ИННОВАЦИОННАЯ СПЕЦИАЛЬНОСТЬ ДЛЯ МАГИСТРОВ
Keywords: energy-saving technologies; transport; infrastructure; Smart roads; Master Program; energy-efficient systems; енергозберігаючі технології; транспорт; інфраструктура; розумні дороги; магістерська програма; енергоефективні системи; энергосберегающие технологии; транспорт; инфраструктура; умные дороги; магистерская программа; энергоэффективные системы; 629.341